Possibilidades de diálogo entre o conceito de ideologia em Bakhtin e a teoria das representações sociais - Machado Júnior, Luiz Bosco Sardinha [UNESP]; Constantino, Elizabeth Piemonte [UNESP] (My University, 2012)
Introducing the theoretical trajectory of social representations theory, outline here the parallel between this theory in social psychology and the Bakhtinian concept of ideology. Both approaches include individual and society as inseparable and views the array of social construction of knowledge forms, related to day-to-day, or composed by formal record of science, as state, religion etc. With this interdisciplinary study, although limited, we hope to contribute to a better understanding of theories that have made important contributions to social psychology, linguistics, ethnography, cultural studies etc.

Apresentando o percurso teórico da teoria das representações sociais, esboçaremos aqui o paralelo entre essa teoria em psicologia social e o conceito bakhtiniano de ideologia. Ambas abordagens compreendem indivíduo e sociedade como indissociáveis e vêem no contato social a matriz da construção de formas de conhecimento, tantos aquelas ligadas ao dia-a-dia, como as compostas pelo registro formal das ciências, do Estado, da religião etc. Com este estudo interdisciplinar, ainda que limitado, esperamos acrescentar à melhor compreensão de teorias que têm trazido importantes contribuições à psicologia social, à lingüística, a etnografia, aos estudos culturais etc.
Possibilities of dialogue between the concept of ideology in Bakhtin and theory of social representations
Keywords: Ideology; Social Representations; Social Psychology; Ideologia; Representações sociais; Psicologia social